Bioactive compounds and carbohydrates in the ‘pacovan’ banana subjected to coating with carnaúba wax (Research, Society and Development, 2020)
The aim of this study was to evaluate the bioactive compounds and carbohydrates in the ‘Pacovan’ banana subjected to coating with carnauba wax, stored at 23 °C and 13 °C. The Bananas were obtained in the city of Bananeiras, Paraiba State, Brazil, collected in the morning, in the totally green maturity stage, with the adoption of Good Agricultural Practices (GAP). In Physiology Post Harvest Laboratory, the fruits were sorted, sanitized and subjected to treatment control (with no covering) and carnauba wax at 5%, 7.5%, and 10%. The evaluations were performed at 0; 2; 4; 6; 8 and 10 days of storage (23 ± 2 °C) and 0; 4; 8; 12; 16 and 20 days (13 ± 1 °C), with the aim of determining the total soluble sugars (TSS), the reducing sugars (RS), the non-reducing sugars (ANR), the ascorbic acid (AA), and the total extractable polyphenols (PET). The temperature of 13 °C provided the fruits of the ‘Pacovan’banana a life extension of more than 8 days, stability in levels of ascorbic acid and polyphenols compared to storage at 23 ºC.